DESCRIPTION OF TRIGICERIDE LEVELS IN HYPERTENSION PATIENTS IN RSUD Dr. MM DUNDA LIMBOTO - Siti Masito R. Ahmad; Rita Amini Warastuti; Fitriyani Rahmatismi Blongkod (LPPM Universitas Bina Mandiri Gorontalo, 2021)
Report on the incidence of hypertension from RSUD Dr. MM Dunda Limboto, that the incidence of hypertension in 2019 in 6 months (July-December) reached 789 people.Hypertension is a health problem that is often found in society and correlates with other diseases. Many factors cause hypertension, one of which is abnormal triglyceride levels or excessive triglyceride levels, This type of research is descriptive quantitative. conducted at the MM Dunda Limboto Regional Hospital with a total sample size of 41 with a purposive sampling technique. Using Univariate data analysis techniques, the results are presented in tabular form. Based on the results of the research conducted, it was found that 31 respondents (75.6%) had triglyceride levels above normal limits (> 150mg/dl) and 10 respondents (24.4%) had normal triglyceride levels (<150mg/dl). The results of this study found that hypertensive patients are thought to have a great chance of having high triglyceride levels, this is in accordance with the results of research that has been done that 31 (75.6%) respondents have high triglyceride levels (>150mg/dl).